High pressure NMR reveals conformational perturbations by disease-causing mutations in amyloid β-peptide. Issue 36 (19th April 2018) - Rosenman, David J.; Clemente, Nicolina; Ali, Muhammad; García, Angel E.; Wang, Chunyu
Abstract : High pressure NMR reveals conformational biases in disease-causing variants of the Aβ monomer. Abstract : Here we present the high pressure NMR characterization of Aβ42 and two Aβ40 variants with Alzheimer-causing mutations E22G and D23N. While chemical shifts only identified localized changes at ambient pressure compared with Aβ40, high pressure NMR revealed a common site with heightened pressure sensitivity at Q15, K16 and L17 in all three variants, which correlates to higher β-propensity at central hydrophobic cluster (CHC) and faster aggregation.